Evaluation of cell death mechanisms induced by the vascular disrupting agent OXi4503 during a phase I clinical trial. - Cummings, J; Zweifel, M; Smith, N; Ross, P; Peters, J; Rustin, G; Price, P; Middleton, MR; Ward, T; Dive, C (2012)
BACKGROUND: OXi4503 is a tubulin-binding vascular disrupting agent that has recently completed a Cancer Research UK-sponsored phase I trial. Preclinical studies demonstrated early drug-induced apoptosis in tumour endothelial cells at 1-3 h and secondary tumour cell necrosis between 6 and 72 h. METHODS: To capture both possible outcomes of OXi4503 treatment on cell death, plasma samples for analysis by M30 and M65 ELISAs, which measure different circulating forms of cytokeratin 18 as biomarkers of apoptosis and necrosis, respectively, were collected from patients entered into the trial at early (4/6 h) and later time points (24h, day 8 and day 15). RESULTS: OXi4503 induced a selective dose-dependent elevation in M30 antigen levels (apoptosis) at 4/6 h and a similar elevation in M65 antigen levels at 24 h (necrosis) consistent with its preclinical cell death profile. For the purposes of investigating potential biomarker relationships to patient characteristics, the trial population was divided into three groups based on radiological and clinical response: (a) early progression, (b) progressive disease and (c) stable disease (SD)/partial response. A significant increase in antigen concentrations was measured by M65 at 24 h in the SD group compared with the two other groups (P=0.015, mean increase 30.9%). CONCLUSION: These results provide pharmacodynamic evidence of drug mechanism of action in cancer patients and highlight the M65 ELISA as a potentially useful biomarker assay of response to OXi4503.